Epigenetic modifications in prostate cancer. (August 2014) - Ngollo, Marjolaine; Dagdemir, Aslihan; Karsli-Ceppioglu, Seher; Judes, Gaelle; Pajon, Amaury; Penault-Llorca, Frederique; Boiteux, Jean-Paul; Bignon, Yves-Jean; Guy, Laurent; Bernard-Gallon, Dominique J
Prostate cancer is the most common cancer in men and the second leading cause of cancer deaths in men in France. Apart from the genetic alterations in prostate cancer, epigenetics modifications are involved in the development and progression of this disease. Epigenetic events are the main cause in gene regulation and the three most epigenetic mechanisms studied include DNA methylation, histone modifications and microRNA expression. In this review, we summarized epigenetic mechanisms in prostate cancer. Epigenetic drugs that inhibit DNA methylation, histone methylation and histone acetylation might be able to reactivate silenced gene expression in prostate cancer. However, further understanding of interactions of these enzymes and their effects on transcription regulation in prostate cancer is needed and has become a priority in biomedical research. In this study, we summed up epigenetic changes with emphasis on pharmacologic epigenetic target agents.